The baseball codes [compact disc, unabridged] : beanballs, sign stealing, and bench-clearing brawls : the unwritten rules of America's pastime - Turbow, Jason (Blackstone Audio, 2010)
Provides a behind-the-scenes analysis of professional baseball's hidden rules, revealing the impact of unwritten codes of conduct, retaliatory behaviors, and cheating, with examples involving such figures as Mickey Mantle, Willie Mays, and Don Drysdale.